1988
DOI: 10.1152/ajpregu.1988.254.6.r1017
|View full text |Cite
|
Sign up to set email alerts
|

Neural control of renal function in edema-forming states

Abstract: To define the role of the renal nerves in renal sodium-retaining edema-forming states, experiments were conducted in conscious chronically instrumented rats with congestive heart failure (myocardial infarction), nephrotic syndrome (adriamycin injection), and hepatic cirrhosis (common bile duct ligation). In each experimental model, renal excretion, as water or sodium, of an acutely administered oral or intravenous isotonic saline load was significantly less than that in control rats. Bilateral renal denervatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 0 publications
10
89
0
Order By: Relevance
“…According to this theory, the sodium retention occurs in a manner identical to that resulting from any other hypovolemic stimulus, and is characterized in part by increases in filtration fraction and renal vascular resistance, enhanced fractional reabsorption offiltrate in the proximal tubule, heightened sympathetic renal nerve activity, activation of the renin-angiotensin system, and a reduced concentration of atrial natriuretic peptide (ANP)' in plasma. Numerous clinical and experimental observations document these patterns ofrenal function in at least some forms of nephrotic syndrome and thereby support the so-called "underfill" mechanism of edema formation (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…According to this theory, the sodium retention occurs in a manner identical to that resulting from any other hypovolemic stimulus, and is characterized in part by increases in filtration fraction and renal vascular resistance, enhanced fractional reabsorption offiltrate in the proximal tubule, heightened sympathetic renal nerve activity, activation of the renin-angiotensin system, and a reduced concentration of atrial natriuretic peptide (ANP)' in plasma. Numerous clinical and experimental observations document these patterns ofrenal function in at least some forms of nephrotic syndrome and thereby support the so-called "underfill" mechanism of edema formation (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 82%
“…This resistance to the natriuretic action of ANP and the blunted natriuresis seen after volume expansion in these rats were shown to improve after renal denervation (7,19). To explore these phenomena further, we have examined the relationship between the natriuretic response to extracellular fluid volume expansion and circulating ANP levels as well as urinary cyclic GMP excretion (an index ofANP bioactivity in the kidneys) in normal and nephrotic rats.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,9 It is well described that the renal sympathetic nerve activity is increased at early stages of cirrhotic liver disease, 2 and when challenged with a sodium load, cirrhotic rats have an impaired ability to excrete sodium, which can be normalized by renal denervation. 2 However, in a micropuncture study in cirrhotic dogs with sodium retention but without ascites, Levy 4 found that single-nephron GFR and delivery of fluid from the late convoluted proximal tubule were unaltered, suggesting that proximal tubular function was normal in these dogs. Similarly, in the present study, as we previously have described in rats with cirrhosis induced by common bile ligation, 5-8 renal lithium handling was normal in rats with early sodium retention.…”
Section: Renal Function During Early Sodium Retention In Cirrhosismentioning
confidence: 99%
“…The left coronary artery ligation model of myocardial infarction in the rat was suitable for this purpose. 60 Within 1-4 weeks after left coronary artery ligation, surviving rats with elevated left ventricular enddiastolic pressure (>15 mm Hg) had reduced cardiac output and failed to increase cardiac output in response to intravenous volume expansion-induced increases in cardiac filling pressure. They exhibited cardiac hypertrophy, hydrothorax, ascites, and peripheral edema.…”
Section: Role Of Renal Nerves In Edema-forming Statesmentioning
confidence: 99%